THE ENHANCEMENT OF STRATEGIC AND OPERATIONAL PERFORMANCE THROUGH ENTERPRISE ARCHITECTURE IN XYZ’S DISTRICT ATTORNEY OFFICES - Frisa Erika; Hudiarto Hudiarto; Sevenpri Candra (Bina Nusantara University, 2013)
The deteriorating image of law enforcement agencies in serving the needs of nowadays community is making the chiefs of XYZ’s district attorney offices to search the best way so that the law service in their offices can be better. This problem is the general reflection of how bad the public service in law’s field is in our country. For that noble purpose, the chiefs see that there is a chance to use the ability of system and information technology. That system is not only for the necessary needs in district attorney office but it is also combined in the existing process in security and court. The chief of office feels that the enhancement performance will be obtained easier if there is the same system and technology and are designed carefully. Within this paper, the researcher uses the framework of Enterprise Architecture to develop the needed system and technology so that it can be realized strategically and operationally much better and can be accounted. The result is the current time conservative service system and have the quality of office automation systems is gradually planned to change into automation for the next two or three years. Therefore, the connection and the cooperation between the attorney, the police and the court will be more harmonic, thus gradually increased the service to the community.